PEMANFAATAN LIMBAH PERTANIAN DAN FESES UNTUK MEDIA HIDUP MAGGOT (Hermetia illucens) SEBAGAI PAKAN SUMBERPROTEIN HEWANI DI PETERNAKAN ARJUNA - Ade Trisna; Yunilas; Muhammad Amran; Muhammad Adanan Purba; Dian Tria Fatmila (LPPI UMN AL WASHLIYAH, 2025)
Agricultural waste and livestock manure that are not properly utilized can cause environmental pollution. This community service aims to reduce environmental pollution through the treatment of agricultural waste and fermented manure to be used as maggot growth media at Arjuna Farm. Maggots are a source of animal protein with good nutritional value, containing 45-50% crude protein. The production of maggots from livestock and agricultural waste can serve as a source of nutrition for livestock. The community service methods include fermenting agricultural waste and manure to create maggot growth media, maggot cultivation training, and the production of dry maggot products that can be used as a source of animal protein feed for poultry. This program also contributes to increasing the income of Arjuna Farm through the produced dry maggot products. It is hoped that through this community service, farmers can access appropriate technology for processing fecal and agricultural waste using fermentation technology to produce a good growth medium for maggots. The results of this service have an impact on environmental preservation and reducing the negative effects of agricultural and fecal waste, as well as contributing to improving their economic welfare. The observation percentages after evaluation at Arjuna Farm were not significantly different from the expected results, with an average of 74% out of 92% in terms of waste processing and farmers' income.